Digital Financial Services as Drivers of Community Development: A Review of Fintech Innovations in Emerging Markets - Haryaman, Adang (KRIEZ ACADEMY : Journal of development and community service, 2024)
This study conducts a comprehensive literature review to analyze the pivotal role of digital financial services (DFS) in advancing community development, particularly within developing countries. Through a meticulous literature-based approach, the paper examines the multifaceted impact of financial technology (fintech) innovations on critical areas such as microfinance delivery, the promotion of digital savings, and the enhancement of lending to small and medium enterprises (SMEs). It systematically discusses how digital platforms and new business models contribute to economic empowerment and foster resilience among low-income populations by addressing long-standing barriers to financial access. The review highlights the opportunities presented by fintech, the key challenges that need to be navigated, and a series of case illustrations from emerging economies. This paper contributes to the discourse on inclusive finance by synthesizing insights on how responsible and context-aware innovation can drive sustainable community-level progress.